Epicardial adipose tissue is associated with left atrial volume and fibrosis in patients with atrial fibrillation - Chahine, Yaacoub; Askari-Atapour, Bahareh; Kwan, Kirsten T.; Anderson, Carter A.; Macheret, Fima; Afroze, Tanzina; Bifulco, Savannah F.; Cham, Matthew D.; Ordovas, Karen; Boyle, Patrick M.; Akoum, Nazem (Frontiers in Cardiovascular Medicine, 2022)
Background: Obesity is a risk factor for atrial fibrillation (AF) and strongly influences the response to treatment. Atrial fibrosis shows similar associations. Epicardial adipose tissue (EAT) may be a link between these associations. We sought to assess whether EAT is associated with body mass index (BMI), left atrial (LA) fibrosis and volume. Methods: LA fibrosis and EAT were assessed using late gadolinium enhancement, and Dixon MRI sequences, respectively. We derived 3D models incorporating fibrosis and EAT, then measured the distance of fibrotic and non-fibrotic areas to the nearest EAT to assess spatial colocalization. Results: 103 AF patients (64% paroxysmal, 27% female) were analyzed. LA volume index was 54.9 [41.2, 69.7] mL/m2, LA EAT index was 17.4 [12.7, 22.9] mL/m2, and LA fibrosis was 17.1 [12.4, 23.1] %. LA EAT was significantly correlated with BMI (R=0.557, p<0.001); as well as with LA volume and LA fibrosis after BSA adjustment (R=0.579 and R=0.432 respectively, p<0.001 for both). Multivariable analysis showed LA EAT to be independently associated with LA volume and fibrosis. 3D registration of fat and fibrosis around the LA showed no clear spatial overlap between EAT and fibrotic LA regions. Conclusion: LA EAT is associated with obesity (BMI) as well as LA volume and fibrosis. Regions of LA EAT did not colocalize with fibrotic areas, suggesting a systemic or paracrine mechanism rather than EAT infiltration of fibrotic areas.